2008
DOI: 10.1097/wnr.0b013e328302c858
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β-peptide levels in laser capture microdissected cornu ammonis 1 pyramidal neurons of Alzheimer's brain

Abstract: Deposition of the amyloid beta-peptide (Abeta) is a pathophysiological event associated with Alzheimer's disease. Although much is known about the molecular composition of extracellular Abeta deposits, the role of the intracellular pool of Abeta is not fully understood. We investigated whether Abeta levels are increased in cornu ammonis 1 pyramidal neurons of Alzheimer's disease hippocampus, using laser capture microdissection to isolate the neurons and enzyme-linked immunosorbent assay for quantification. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 26 publications
(29 reference statements)
2
36
0
1
Order By: Relevance
“…This finding is in line with several previous studies reporting the presence of iAβ in the AD brains [3,4,[7][8][9]11,15,17,19,22,23,39]. In 2008, Aoki and colleagues, while using laser capture micro dissection to isolate neurons of hippocampus, noted iAβ 42 in all investigated subjects [50]. They detected a significant increase in the level of iAβ 42 in AD subjects when compared with controls (mean age ranging from 71 to 90) and the highest levels were seen in subjects with familial disease [50].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding is in line with several previous studies reporting the presence of iAβ in the AD brains [3,4,[7][8][9]11,15,17,19,22,23,39]. In 2008, Aoki and colleagues, while using laser capture micro dissection to isolate neurons of hippocampus, noted iAβ 42 in all investigated subjects [50]. They detected a significant increase in the level of iAβ 42 in AD subjects when compared with controls (mean age ranging from 71 to 90) and the highest levels were seen in subjects with familial disease [50].…”
Section: Discussionsupporting
confidence: 78%
“…In 2008, Aoki and colleagues, while using laser capture micro dissection to isolate neurons of hippocampus, noted iAβ 42 in all investigated subjects [50]. They detected a significant increase in the level of iAβ 42 in AD subjects when compared with controls (mean age ranging from 71 to 90) and the highest levels were seen in subjects with familial disease [50]. Thus, the lack of IR in the brains obtained from subjects without neuronal degeneration may indicate that the level of the iAβ is very low, undetectable at the light microscopic level by IHC methods.…”
Section: Discussionmentioning
confidence: 99%
“…Not all A␤ variants are toxic, and it has been suggested that shorter variants such as A␤40 could be protective (7). For instance, the pyramidal neurons that become affected in AD show elevated levels of A␤42 but not A␤40 (8). In accord with this notion are the familial presenilin mutations, which in many cases result in decreased total A␤ production but an increased A␤42/40 ratio (9).…”
mentioning
confidence: 53%
“…Neuropathological analyses of some family members revealed strong extracellular plaque pathology, severe cerebral amyloid angiopathy, as well as substantial Aβ x-40 accumulation in the dentate gyrus and the CA1-CA2 subfield of the hippocampus (Cabrejo et al, 2006). Increased Aβ 42 levels, as well as a significantly increased Aβ42/Aβ40 ratio compared to controls, could also be demonstrated in CA1 pyramidal neurons of AD patients which have been isolated from post-mortem brain samples by laser-capture microdissection (Aoki et al, 2008). These data have been recently verified in Purkinje cell neurons from sporadic AD patients using a sensitive ELISA (Hashimoto et al, 2010).…”
Section: Intraneuronal Aβ Pathology In Admentioning
confidence: 93%